2016
DOI: 10.1007/s00423-016-1470-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis comparing partial stomach partitioning gastrojejunostomy versus conventional gastrojejunostomy for malignant gastroduodenal obstruction

Abstract: PSPGJ for MGO seems to offer significant advantages in terms of alleviating DGE and improving postoperative recovery compared to CGJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
19
0
3
Order By: Relevance
“…Kumagai et al[28] published a meta-analysis comparing GP with GJ. Seven studies containing 207 patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…Kumagai et al[28] published a meta-analysis comparing GP with GJ. Seven studies containing 207 patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…The stent delivery system involved insertion over the guide wire through the working channel for the placement of the uncovered SEMS at the obstructive lesion. GJY was performing using conventional side-to-side gastrojejunostomy or modified Divine gastrojejunostomy as previously described ( 5 , 6 ), with the method selected by the operator.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with malignant GOO develop undesirable clinical symptoms, such as nausea, vomiting, abdominal pain, and difficulty eating, leading to a poor quality of life. Gastrojejunostomy has been performed to resolve these obstruction-induced clinical symptoms ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 A meta-analysis of retrospective studies showed partial stomach-partitioning significantly decreased the risk of delayed gastric emptying (DGE) after gastrojejunostomy for malignant GOO although the mechanism has not been elucidated yet. 13 Outcomes Table 1 shows outcomes of biliary and gastrointestinal double bypass from the literature. 4,6,7,9,10,[14][15][16][17][18][19][20][21][22] Among the 14 studies, two were prospective randomized controlled trials (RCTs) comparing double bypass and biliary bypass alone, 14,15 eight studies were retrospective comparative studies 4,7,10,[16][17][18][19][20] and the remaining were case series.…”
Section: Surgical Proceduresmentioning
confidence: 99%